An early‐diverging procolophonid from the lowermost Triassic of South America and the origins of herbivory in Procolophonoidea. (28th February 2021) - Pinheiro, Felipe L.; Silva‐Neves, Eduardo; Da‐Rosa, Átila A. S.
Abstract: Procolophonoidea was the only parareptile clade to survive the end‐Permian mass extinction, and they experienced a major adaptive radiation during the Triassic. The flourishing of procolophonoid lineages in highly stressful post‐extinction environments may be, at least in part, a result of their early adaptations to herbivory, which would eventually become the most common feeding strategy in later representatives of the group. Although procolophonoids are comparatively diverse in the South African Lystrosaurus declivis Assemblage Zone, only the Gondwanan widespread taxon Procolophon trigoniceps has been thus far reported in South American deposits of similar age. Here, we present a new procolophonid genus and species from the Lower Triassic Sanga do Cabral Formation of Brazil. Oryporan insolitus gen. et sp. nov. combines typical adaptations suggestive of herbivory with primitive character states that are peculiar to early procolophonoids. Accordingly, phylogenetic analysis places the new species as an early‐diverging procolophonid, thus far the phylogenetically earliest to develop apparent adaptations for herbivory. Character optimization shows that the bulbous, labiolingually expanded molariforms of most procolophonids (usually interpreted as indicative of high‐fibre herbivory) were co‐opted from an insectivorous dentition. The new taxon also highlights the diversity of feeding habits displayed by Early Triassic procolophonoids, which was probably crucial for the survival of the clade in post‐extinction disaster communities.